Arabidopsis DNA polymerase lambda mutant is mildly sensitive to DNA double strand breaks but defective in integration of a transgene - Furukawa, Tomoyuki; Angelis, Karel J.; Britt, Anne B. (Frontiers in Plant Science, 2015)
The DNA double-strand break (DSB) is a critical type of damage, and can be induced by both endogenous sources (e.g. errors of oxidative metabolism, transposable elements, programmed meiotic breaks, or perturbation of the DNA replication fork) and exogenous sources (e.g. ionizing radiation or radiomimetic chemicals). Although higher plants, like mammals, are thought to preferentially repair DSBs via nonhomologous end joining (NHEJ), much remains unclear about plant DSB repair pathways. Our reverse genetic approach suggests that DNA polymerase λ is involved in DSB repair in Arabidopsis. The Arabidopsis T-DNA insertion mutant (atpolλ-1) displayed sensitivity to both gamma-irradiation and treatment with radiomimetic reagents, but not to other DNA damaging treatments. The atpolλ-1 mutant showed a moderate sensitivity to DSBs, while Arabidopsis Ku70 and DNA ligase 4 mutants (atku70-3 and atlig4-2), both of which play critical roles in NHEJ, exhibited a hypersensitivity to these treatments. The atpolλ-1/atlig4-2 double mutant exhibited a higher sensitivity to DSBs than each single mutant, but the atku70/atpolλ-1 showed similar sensitivity to the atku70-3 mutant. We showed that transcription of the DNA ligase 1, DNA ligase 6, and Wee1 genes was quickly induced by BLM in several NHEJ deficient mutants in contrast to wild-type. Finally, the T-DNA transformation efficiency dropped in NHEJ deficient mutants and the lowest transformation efficiency was scored in the atpolλ-1/atlig4-2 double mutant. These results imply that AtPolλ is involved in both DSB repair and DNA damage response pathway.